Capital Structure Determinants: New Evidence from the MENA Region Countries - Ben Hamouda, Raja Zekri; Hamzaoui, Nessrine; Jilani, Faouzi (International Journal of Economics and Financial Issues, 2023)
The objective of this paper is to investigate empirically the determinants of capital structure for a sample of 1101 firms from 11 MENA region countries over the period 2003-2017. Using a comparative approach, we find that firm-specific determinants explain better differences in capital structure choices than other country-specific determinants. Comparisons between countries, sub-regions (GGC and non-GCC countries) and legal origin (Common and Civil law countries) show furthermore that there are differences in terms of significance and importance of capital structure determinants. The most important determinant in the MENA region is profitability. The firm’s capital structure is positively impacted by size, tangibility of assets and private credit and it is negatively impacted by profitability, growth opportunities, GDP growth rate and stock market capitalization as a proportion of GDP. Moreover, we find that total leverage ratio, expressed in market values, give better results than leverage ratio expressed in book values and long-term leverage ratios expressed in book and/or market values. Finally, there is some evidence that the “Jasmine Revolution” has had an impact on firms’ capital structure determinants. Specific-level determinants play a much more prominent role after the revolution than in the past.